Fiscal rules and optimal currency composition of sovereign debt in emerging economies - Oscar M. Valencia; Luis Alberto Rodriguez; Juan Pablo Siachoque (Inter-American Development Bank (IDB), 2023)
Total public debt in most emerging markets grew before and after the pandemic with a sizable share in foreign currency. Along this trend, interest payments increased even in the presence of active fiscal rules in some countries. How should debt management of public debt be set under a fiscal rule? This document studies how optimal currency composition reduces the cost of debt and facilitates fiscal rule compliance but increases budget risk. Using a small open economy model, we provide evidence that optimal foreign currency holdings in Chile, Colombia and Mexico depart considerably from observed; remaining low (high) in periods of favorable (adverse) external or domestic macroeconomic and financial conditions.
Keywords: E61; E62; H63; 330; sovereign debt management; fiscal rules; currency composition